Procedures for Complete Systematic Land Registration on Land Ownership Rights in Karawang Regency - Sambuaga, Jefferson Asprila; Farma Rahayu, Mella Ismelina (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
The Complete Systematic Land Registration (PTSL) program ideally provides legal certainty over land ownership, particularly in rapidly developing areas such as Karawang Regency. However, in reality, challenges remain in its implementation, such as the varying quality of services, which can hinder the achievement of the program's objectives. This study aims to examine the implementation of PTSL in providing legal certainty over land rights in Karawang Regency. The research employs a Normative Juridical method with a Descriptive Analytical approach. The findings indicate that the implementation of PTSL has been carried out in accordance with the provisions regarding the object, subject, basis of rights, processes, and financing. The program offers strategic benefits in supporting legal certainty, although its success largely depends on improving the quality of public services provided by relevant institutions.